Reading Culture in Building Human Development Index: Analysis in Serdang Bedagai District - Muhammad arief adillah; Khasan Effendy; Ismiyarto; Ella Wargadinata (Universitas Medan Area, 2023)
The culture of reading is something that Indonesia has been striving for until now because it is not only a big achievement for future generations but also has an impact on the Human Development Index, which has so far been lagging behind other countries. This research was conducted using the Systematic Literature Review (SLR) method with a database that the researchers had previously determined. As for the formulation of the problem in this study is how the culture of reading in building the human development index: analysis in Serdang Bedagai District. The results of the study show that 2 points can be an option for a reading culture in Serdang Bedagai Regency, namely the use of pedagogic methods and also the encouragement of students' motivation towards a reading culture.